LEADERSHIP SKILLS AND ITS RELATION TO EMPLOYEES' JOB PERFORMANCE: FINDINGS FROM THE STUDY AT THE MINISTRY OF WOMEN, FAMILY AND COMMUNITY DEVELOPMENT AT PUTRAJAYA - Marni Haji Ghazali; Wan Nor Azleen Wan A. Rahman, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study was conducted with the aim to examine the relationship between leadership skills and employees job performance in the Ministry of Women, Family and Community Development in Putrajaya. In this study, the research objective is (i) to identify the level of employee’s job performance, (ii) to examine the relationship between leadership skills of a leader’s measured in terms of communication skills, motivation skills, interpersonal skills and technical skills towards employee’s job performance and lastly (iii) to determine the significant predictor of leadership skills on employees' job performance. Data was collected through a structured questionnaire from 90 respondents. The main analysis involved descriptive and inferential statistics in order to achieve the research objectives of the study. The study findings have revealed that the level of employee’s job performance is high meanwhile results from Pearson Correlation and Multiple regression analysis also have confirmed that there is significant and positive relationship between leadership skills of a leader towards employees job performance in the Ministry.